Nutrition-sensitive food systems and biofortified crops - Chandra S R Nuthalapati; P K Joshi; Bhaskar Mittra; Prabhu Pingali (Agricultural Economics Research Review, 2023)
The realization that economic growth is a necessary but insufficient condition for improving the nutritional status has led to a paradigm shift in addressing malnutrition through nutrition-sensitive development. Biofortification is one such nutrition-sensitive food system intervention designed to supply crucial micronutrients through staple diets to undernourished populations that may not otherwise be able to consume diversified diets. Biofortified foods can provide 35–50% of the daily estimated average requirement of micronutrients. Biofortification is still at a nascent stage, however, and the state may help in developing a value chain for biofortified. The paper discusses pragmatic policy interventions in that direction.